Krisis Biodiversitas Perairan: Investigasi Solusi Berbasis Komunitas untuk Pemulihan Ekosistem Aquatik - Okniel Zebua; Asokhiwa Zega; Ratna Dewi Zebua; Destriman Laoli; Januari Dawolo; Betzy Victor Telaumbanua (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
Crisis aquatic biodiversity is a critical environmental issue, triggered by human activities such as overfishing, pollution, and climate change, which have serious impacts on the stability of ecosystems and the climate change, which has serious impacts on the stability of ecosystems and the livelihoods of coastal communities. livelihoods of coastal communities. This research aims to examine community-based solutions in restoring degraded aquatic ecosystems, with a focus on the integration of sustainable aquaculture technologies and aquaponic systems. The methodology used was a comprehensive literature analysis of scientific articles, journals and relevant publications. The research findings show that sustainable fisheries management, habitat restoration, environmental education and awareness, implementation of environmentally education and environmental awareness, the application of environmentally friendly technologies, and the development of supportive policies are the main strategies for sustainable fisheries management. development of supportive policies are key strategies in improve conservation effectiveness. The implications of this research show that a community-based approach is not only effective for the conservation of aquatic biodiversity, but also provides practical guidance for policymakers and non-governmental organizations in designing and implementing community-based policy makers and non-governmental organizations in designing and implementing more holistic and effective ecosystem restoration programs that are more holistic and sustainable.